Self lubrication of pressureless sintered SiC ceramics - Wei Zhang; Seiji Yamashita; Hideki Kita (Journal of Materials Research and Technology, 2020)
The self lubrication of SiC ceramics prepared by pressureless sintering was investigated by annealing at different temperatures in air. It was found that low coefficient of friction can be obtained for SiC ceramics by annealing, and the coefficient of friction of SiC ceramics decreased with the increase of annealing temperature. The SiC ceramics with annealing at 1500 °C revealed the best self lubricating property, with the coefficient of friction of 0.4, while the coefficient of friction of SiC ceramics without annealing was as high as 0.7. The SiC ceramics with annealing at 1000 °C can show self lubrication over a long sliding distance without increasing wear. The formation of α-cristobalite on the annealed SiC ceramics can further lubricate SiC ceramics and shorten run in period. Self lubrication mechanism of SiC ceramics with annealing is considered that on the one hand, the formation of silicon oxide layers after annealing can reduce the number of SiC grains directly exposed to the sliding interface in the early stage of the sliding, decreasing the number of hard SiC wear particles formed on the sliding interface; and on the other hand, silicon oxide wear particles generated by the wear of the silicon oxide layers formed by annealing can be used as solid lubricant.